DESAIN UI/UX APLIKASI BERGERAK INTEGRATIF MANAJEMEN MULTIMASJID RAMAH TAKMIR MENGGUNAKAN METODE DESAIN THINKING - Siti Umi Nurhavizza, Siti Umi Nurhavizza; Ari Sujarwo (Teknosia, 2024)
The mosque serves as a center for community development, the cornerstone of Islamic society, and the foundation of civilization. According to data from the Ministry of Religious Affairs through the SIMAS (Masjid Information System) application, there were 242,832 mosques and 269,076 prayer rooms in Indonesia as of 2022. However, mosques and prayer rooms in Indonesia face issues like low activity levels and management often dominated by elderly individuals. Therefore, this research aims to design an integrative multi-mosque management application specifically for mosque caretakers (takmir) to manage mosques effectively and make them centers of community activities. This study uses the Design Thinking method, consisting of five stages: empathize, define, ideate, prototyping, and testing. The result is the design of a mosque management application named Kaffah, with seven main features: congregation data, congregation activities, mosque staff data, calendar, takmir, event list, and event data. These features are expected to assist takmir in managing the mosque and congregation data, the mosque becomes bustling with visitors and making the mosque a hub for community activities. Testing the Kaffah application's interface design shows that the developed prototype successfully aids and meets the needs of takmir in managing mosques.